KAJIAN IN SILICO INTERAKSI ANTARA PIPERIN, MANGOSTIN, DAN KURKUMIN DENGAN KARAGENAN - Wiwin Winingsih; Pebry Purnamasari (Sekolah Tinggi Farmasi Indonesia, 2023)
Mangosteen, curcumin and piperine are compounds that have various pharmacological activities but have low solubility in water. To increase their solubility, several methods were available, one of it was inclusion complex formation. Inclusion complex consist of guest molecule and host molecule as complexing agent. Complexing agents that have been widely used was cyclodextrin, the use of carrageenan as a host for mangosteen, curcumin and piperine has never been reported . This research aimed to study the interaction between carrageenan with mangosteen, curcumin and piperine and compare it with cyclodextrins by in silico method. This research can be used to design inclusion complex of those three compounds with carrageenan. This study was carried out by molecular docking. USCF Chimera® 1.12 and Autodock® Vina software were used to study the interaction between mangosteen, curcumin and piperine as ligands with kappa carrageenan, iota carrageenan and beta-cyclodextrin as receptors. Docking results showed that these compound had good interaction with carrageenan as well as cyclodextrin by the formation hydrogen bonds, van der walls and ionic bonds.